Реши уравнение 5 – 2(x – 4) = 3(5 – x) – 4x

0 голосов
21 просмотров

Реши уравнение 5 – 2(x – 4) = 3(5 – x) – 4x


Алгебра (27 баллов) | 21 просмотров
Дано ответов: 2
0 голосов
Правильный ответ

5-2(х-4)=3(5-х)-4х

5-2х+8=15-3х-4х

13-2х=15-7х

-2х+7х=15-13

5х=2

х=2:5

х=0,4                             

5-2(0,4-4)=3(5-0,4)-4*0,4

5-2*(-3,6)=3*(4,6)-1,6

      5+7,2=13,8-1,6

       12,2=12,2

Ответ: 0,4.

 

(84.6k баллов)
0 голосов

5-2(х-4)=3(5-х)-4х;

5-2х+8=15-3х-4х;

-2х+3х+4х=15-5-8;

5х=2;

х=0,4.

(7.3k баллов)